Written corrective feedback on students’ thesis writing: an analysis of student-supervisory interactions - Adrefiza Adrefiza; Fortunasari Fortunasari (UPT Bahasa Universitas Tanjungpura, 2020)
This study examines written corrective feedback (WCF) provided by the lecturers on their supervisee-students' thesis drafts at the English Education Program, Faculty of Education, Jambi University. Following Kumar and Stracke (2007), the analysis focuses on the types and distribution of WCF by Holmes' (2008) three main categories of speech acts: (a) Referential (editorial, organization, content); (b) Directive (suggestion, question, instruction); and (c) Expressive (praise, criticism, opinion). The use of non-linguistic features such as question mark, interjection, circle, and underline was also identified to see the supervisors' emotional expressions during the interactions. The findings show that Referential was the most frequent types of WCF identified (131 out of 271 or 48.3 %), followed by Directive (107 or 39.5 %). Expressive, on the other hand, was not very common with only 33 instances (12.2%) found in the data. Overall, the majority of the lecturers' WCF were dominated by the use of Editorial (102 = 37.6 %) but with a very limited number of Opinion (4 = 1.5%)) and Content (6 = 2.2%). A total number of 394 non-linguistic symbols were identified along with the lecturers' WCF to show their personal and psychological expressions. Apart from its frequent absence in many students' writing assignments, the provision of WCF on the students' writing does not only play a key role in improving the students' writing but also accelerates their self-directed learning.